A efetividade dos direitos antidumping no Brasil: possibilidade de utilização das medidas como barreira à entrada - Wentz, Jonas Roberto (Universidade do Vale do Rio dos Sinos, 2021)
The growth of international trade, triggered by the globalization of the economy, has led to an explosion in the use of anti-dumping measures, which have consolidated themselves as an important defense mechanism for the national industry in the fight against unfair trade carried out through imports at a dumping price. The increase in the use of this mechanism has raised questions about its effectiveness. In this content, the present study aims to analyze the effectiveness of anti-dumping rights in Brazil, considering the possibility that the measures may have been used as a barrier mechanism to the entry of goods, benefiting a domestic industry that operates in highly concentrated and monopolistic markets, to the detriment of importers and consumers, among other related parties. The present study has a scientific character of an applied nature, aiming to produce knowledge to solve specific problems related to anti-dumping duties, using the base theory of economic analysis of law. The proposed research made use of bibliographic review techniques and statistical analysis applied to law. Regarding the examination of the collected data, the research approach is qualitative and quantitative. Qualitative in the sense of identifying the profile of the domestic industry benefited by the antidumping measures in Brazil, and quantitative in the sense of raising in what quantity and percentage these industries make use of the measures. Confirmed the hypothesis of concentration of the benefited industry and the possible abusive use of anti-dumping rights, even at the theoretical level, moving to the analysis of the rules for the evaluation of the public interest presented as a possible counterbalance to the effects of the indiscriminate application of anti-dumping measures.
Keywords: Dumping; Medidas antidumping; Protecionismo; Interesse público; Antidumping measures; Protectionism; Public interest; ACCNPQ::Ciências Sociais Aplicadas::Direito